2014
DOI: 10.1177/193758671400700406
|View full text |Cite
|
Sign up to set email alerts
|

Centralized vs. Decentralized Nursing Stations: An Evaluation of the Implications of Communication Technologies in Healthcare

Abstract: Hospital, interdisciplinary, nursing, technology, work environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…The effectiveness of other types of communication technologies has also been tested. For example, Nurse Call Systems (NCSs) provide patients with a more natural and faster way to communicate with nurses; through NCSs, patients press a button on the bed, which turns on a light outside of a patient's room and on the bed station, showing which patient needs help Similarly, Guarascio-Howard (2011) found that wireless communication technology with audio and visual capabilities to facilitate communication between nurses and patients as well as among nurses improved the responses to patients falls from hospital beds, reduced cell phone usage among nurses and increased efficiency (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of other types of communication technologies has also been tested. For example, Nurse Call Systems (NCSs) provide patients with a more natural and faster way to communicate with nurses; through NCSs, patients press a button on the bed, which turns on a light outside of a patient's room and on the bed station, showing which patient needs help Similarly, Guarascio-Howard (2011) found that wireless communication technology with audio and visual capabilities to facilitate communication between nurses and patients as well as among nurses improved the responses to patients falls from hospital beds, reduced cell phone usage among nurses and increased efficiency (7).…”
Section: Resultsmentioning
confidence: 99%
“…The NCSS system as already mentioned, this system can improve nurses' responses to patients, so that it can reduce the number of patients falling out, thus work efficiency can be assessed to increase with this system (7).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies indicated a significant decrease in agreement that the unit layout supports teamwork after decentralization: one assessing three units (centralized M ¼ 4.72, 4.63, 4.15;decentralized M ¼ 2.25, 3.18, 2.86;p ¼ .05;Pati et al, 2015) and one overall (centralized M ¼ 4.21, decentralized M ¼ 2.94, p ¼ .00; Fay et al, 2017). Finally, Bayramzadeh and Alkazemi (2014) found that nurses on decentralized compared to centralized units had lower disagreement that most communication was face-to-face in their unit (centralized M ¼ 2.15, SD ¼ 0.87; decentralized M ¼ 1.77, SD ¼ 0.68, p ¼ .034). Nurses on the decentralized compared to centralized units also had higher disagreement that most communications between nursing stations occur through technology (centralized M ¼ 3.10, SD ¼ 0.79; decentralized M ¼ 3.60, SD ¼ 0.91, p ¼ .017 ;Bayramzadeh & Alkazemi, 2014).…”
Section: Collaboration and Communicationmentioning
confidence: 99%
“…However, Bayramzadeh and Alkazemi (2014) found communication was more frequent among staff working on a decentralized unit compared to those working on a centralized unit. This may have been due to the shared workload across the unit and staff staying together at the smaller stations, which not only increased communication but increased collaboration as well (Bayramzadeh & Alkazemi, 2014). Pati, Harvey, Redden, Summers, and Pati (2015) investigated staff performance on a hematology unit that transitioned from a centralized to a decentralized model.…”
mentioning
confidence: 99%